ADHD, social skills and risky internet use among elementary school children - DERİN S.; Celik S.; Selman S. B. (My University, 2025)
Background: Previous studies have established a link between Attention-Deficit/Hyperactivity Disorder (ADHD) and risky internet use (RIU); however, the processes underlying this association remain unclear. This study examines whether a proportion of the association between ADHD and RIU was shared with social skills. Methods: The sample included 142 children aged 6–12 years (65% female, M = 8.5, SD = 1.7), comprising 71 children diagnosed with ADHD and 71 controls without ADHD. Standardized assessments were administered to measure RIU and social skills. Path analysis was employed to evaluate the association among ADHD, social skills, and RIU. Key demographic variables, including gender, birth timing, age of speech onset, household income, parental education, and number of siblings, were controlled for in the analyses. Results: An ADHD diagnosis was significantly associated with reduced social skills (β = − 1.68, p < 0.001), and reduced social skills was strongly linked to higher levels of RIU (β = − 0.57, p = 0.004). The direct association between ADHD and RIU was not statistically significant (β = − 0.52, p = 0.169). However, a significant indirect effect was observed, indicating that ADHD-RIU link was shared with reduced social skills (β = 0.96, p = 0.004). Conclusions: The findings indicate that a significant proportion of the association between ADHD and RIU was shared with social skills, emphasizing the importance of social skills as a potential factor for RIU risk in children with ADHD. Interventions that focus on enhancing social skills may support efforts to address RIU in this population.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Psikiyatri; Pediatri; Clinical Medicine (Med); Clinical Medicine; Psychiatry; Pediatrics; Pediatri, Perinatoloji ve Çocuk Sağlığı; Psikiyatri ve Ruh Sağlığı; Pediatrics, Perinatology and Child Health; Psychiatry and Mental Health; ADHD; Elementary school children; Risky internet use; Social skills